UAA and UAG may Encode Amino Acid in Cathepsin B Gene of Euplotes octocarinatus. (2nd September 2019) - Wang, Ruanlin; Liu, Jingni; Di Giuseppe, Graziano; Liang, Aihua
Abstract: The ciliate Euplotes deviates from the universal genetic code by translating UGA as cysteine and using UAA and UAG as the termination codon. Here, we cloned and sequenced the Cathepsin B gene of Euplotes octocarinatus ( Eo‐CTSB ) which containing several in‐frame stop codons throughout the coding sequence. We provide evidences, based on 3′‐RACE method and Western blot, that the Eo‐CTSB gene is actively expressed. Comparison of the derived amino acid sequence with the homologs in other eukaryotes revealed that UAA and UAG may code for glutamine in Eo‐CTSB . These findings imply an evolutionary complexity of stop codon reassignment in eukaryotes.